Long noncoding RNA NEAT1/microRNA‐125a axis predicts increased major adverse cardiac and cerebrovascular event risk independently in patients with unprotected left main coronary artery disease underwent coronary artery bypass grafting. Issue 7 (17th March 2020) - Liu, Haining; Yan, Xiulian; Yu, Jingbin
Abstract: Background: The study aimed to investigate the long noncoding RNA nuclear‐enriched abundant transcript 1 (lnc‐NEAT1) and microRNA‐125a (miR‐125a) expressions, and further explore the role of lnc‐NEAT1/miR‐125a axis in predicting major adverse cardiac and cerebrovascular event (MACCE) risk in patients with unprotected left main coronary artery disease (ULMCAD) underwent coronary artery bypass grafting (CABG). Methods: A total of 280 patients with ULMCAD underwent CABG were consecutively enrolled in our prospective study, and their plasma samples were collected before CABG for the detection of lnc‐NEAT1 and miR‐125a expressions by reverse transcription quantitative polymerase chain reaction. Lnc‐NEAT1/miR‐125a axis was calculated via dividing lnc‐NEAT1 by miR‐125a. After CABG, regular follow‐up was continued until MACCE occurrence or 36 months. Results: Lnc‐NEAT1 expression, miR‐125a expression, and lnc‐NEAT1/miR‐125a axis were 0.998 (IQR: 0.440‐1.720, range: 0.116‐5.771), 0.997 (IQR: 0.461‐1.650, range: 0.055‐3.621), and 1.018 (IQR: 0.384‐2.782, range: 0.041‐52.832), respectively. And lnc‐NEAT1 was negatively associated with miR‐125a. The 1‐, 2‐, and 3‐year MACCE occurrence was 19 (6.8%), 29 (10.4%), and 38 (13.6%), respectively. Lnc‐NEAT1/miR‐125a axis ( χ 2 = 11.207, P = .001) and lnc‐NEAT1 expression ( χ 2 = 5.345, P = .021) positively associated with accumulating MACCE occurrence, while miR‐125a expression ( χ 2 = 5.869, P = .015) negatively correlated with accumulating MACCE occurrence. Notably, lnc‐NEAT1/miR‐125a axis presented numerically better predictive value compared with lnc‐NEAT1 or miR‐125a alone for MACCE risk. Furthermore, lnc‐NEAT1/miR‐125a axis high, elderly age, increased BMI, diabetes, previous stroke, LVEF, and higher disease extent (all P < .05) were independent predictive factors for increased accumulating MACCE occurrence. Conclusion: Lnc‐NEAT1/miR‐125a axis, as a combined index, presents potential value to be a prognostic biomarker for MACCE risk in ULMCAD management.